Initial results of LF sensor network for lightning observation and characteristics of lightning emission in LF band. Issue 21 (12th November 2014) - Yoshida, Satoru; Wu, Ting; Ushio, Tomoo; Kusunoki, Kenichi; Nakamura, Yoshitaka
Abstract: We have been developing an LF sensor network called Broadband Observation network for Lightning and Thunderstorm (BOLT), to image the structure of lightning discharges in 3D using time of arrival (TOA) technique. This paper documents initial results and characteristics of BOLT source locations for further understanding of LF radiation associated with lightning. Theoretical reduced Chi‐square distribution fitted to BOLT observation data indicates a root mean square (rms) timing error of about 200 ns for each sensor. Monte Carlo simulations of BOLT indicate that at an altitude of 5000 m the standard deviations for horizontal differences between a known source and a location that the BOLT algorithm produces are less than 200 m, and vertical differences are less than 400 m in most of the network. Furthermore, comparison of BOLT and VHF source locations arriving at the same site within 5 µs indicates that the average difference for elevation direction is 0.73° with a standard deviation of 3.64°, and that for the azimuth direction is 0.58° with a standard deviation of 1.98°. Lightning flash processes of intracloud (IC) and cloud‐to‐ground (CG) flashes, including preliminary breakdown pulses, negative leaders, breakdown in the negative charge region (NCR), and an attempted leader, are well imaged by BOLT. Normalized amplitudes in E‐field change waveform of BOLT sources associated with negative leaders and breakdown occurred in the NCR do not have significant difference, implying that most BOLT sources in the NCR might be associated with negative recoil leaders. Key Points: A newly developed LF sensor network produces clear 3D images of lightning Time of arrival technique for lightning works well on signals in LF band Most LF sources in negative charge region might be related to recoil leaders